A Study on the Relationship between Prices of Lac and Quantity Exported - Ratna Rao, A. (Indian Forester, 1992)
The relation between quantity of lac exported and international price of lac is found to be expressible in the form y = 10.94 - 0.0382 x - 0.11012 x2 with reasonable accuracy.